News media exposure and life satisfaction in the COVID-19 pandemic: a moderated mediation model of COVID-19 fear and worries and gender - Magdalena Iwanowska; Anna Maria Zawadzka; Blanka Kondratowicz (Current Issues in Personality Psychology, 2023)
Background Research has found that news media exposure may have both positive and negative consequences for well-being in times of crisis. However, the internal mechanisms underlying that relationship need further investigation. The pur-pose of the research presented in the paper was to explore the role of COVID-19 fear and worries and users’ gender in the relationship between news media exposure and life satisfaction.